NCAR Release of CAM‐SE in CESM2.0: A Reformulation of the Spectral Element Dynamical Core in Dry‐Mass Vertical Coordinates With Comprehensive Treatment of Condensates and Energy. (17th July 2018) - Lauritzen, P. H.; Nair, R. D.; Herrington, A. R.; Callaghan, P.; Goldhaber, S.; Dennis, J. M.; Bacmeister, J. T.; Eaton, B. E.; Zarzycki, C. M.; Taylor, Mark A.; Ullrich, P. A.; Dubos, T.; et al.
Abstract: It is the purpose of this paper to provide a comprehensive documentation of the new NCAR (National Center for Atmospheric Research) version of the spectral element (SE) dynamical core as part of the Community Earth System Model (CESM2.0) release. This version differs from previous releases of the SE dynamical core in several ways. Most notably the hybrid sigma vertical coordinate is based on dry air mass, the condensates are dynamically active in the thermodynamic and momentum equations (also referred to as condensate loading), and the continuous equations of motion conserve a more comprehensive total energy that includes condensates. Not related to the vertical coordinate change, the hyperviscosity operators and the vertical remapping algorithms have been modified. The code base has been significantly reduced, sped up, and cleaned up as part of integrating SE as a dynamical core in the CAM (Community Atmosphere Model) repository rather than importing the SE dynamical core from High‐Order Methods Modeling environment as an external code. Key Points: The CESM2.0 release of the spectral element dynamical core (CAM‐SE) is documented Model has comprehensive treatment of condensates and energy The CAM‐SE model has been sped up significantly compared to its predecessor CAM‐HOMME